2017
DOI: 10.1074/jbc.m116.752543
|View full text |Cite
|
Sign up to set email alerts
|

TRIM24 protein promotes and TRIM32 protein inhibits cardiomyocyte hypertrophy via regulation of dysbindin protein levels

Abstract: We have previously shown that dysbindin is a potent inducer of cardiomyocyte hypertrophy via activation of Rho-dependent serum-response factor (SRF) signaling. We have now performed a yeast two-hybrid screen using dysbindin as bait against a cardiac cDNA library to identify the cardiac dysbindin interactome. Among several putative binding proteins, we identified tripartite motif-containing protein 24 (TRIM24) and confirmed this interaction by co-immunoprecipitation and co-immunostaining. Another tripartite mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 65 publications
1
29
0
Order By: Relevance
“…TRIM72 exerts cardiac protective effects by interacting MG53‐dependent caveolin‐3 with phosphatidylinositol 3 kinase and by subsequent activation of the reperfusion injury salvage kinase pathway (Cao et al, ). TRIM32 inhibits cardiomyocyte hypertrophy by degrading dysbindin, a potent inducer of cardiomyocyte, in neonatal rat ventricular cardiomyocytes (Borlepawar et al, ). Here, we provide evidence of a close relationship between TRIM72 and cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…TRIM72 exerts cardiac protective effects by interacting MG53‐dependent caveolin‐3 with phosphatidylinositol 3 kinase and by subsequent activation of the reperfusion injury salvage kinase pathway (Cao et al, ). TRIM32 inhibits cardiomyocyte hypertrophy by degrading dysbindin, a potent inducer of cardiomyocyte, in neonatal rat ventricular cardiomyocytes (Borlepawar et al, ). Here, we provide evidence of a close relationship between TRIM72 and cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, TRIM17 binds to BCL2A1 and prevents TRIM28-meidiated ubiquitination and degradation of BCL2A1 in melanoma cells [44]. Besides, TRIM24 is shown to inhibit the degradation of dysbindin in cardiomyocytes in a similar manner [45].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of TRIM24 have mainly focused on its role in multiple forms of tumorigenesis [88][89][90][91][92]. However, the functions of TRIM24 in the heart have recently been demonstrated by Borlepawar et al [93], who found that TRIM24 acts as a protector of dysbindin, a prohypertrophic protein, to diminish degradation by TRIM32. The authors extrapolated their conclusions based on the observation that the level of TRIM24 was noticeably upregulated in hypertrophic or dilated mouse and human hearts.…”
Section: Trim24mentioning
confidence: 99%
“…Recent studies have shown that many members of the TRIM superfamily are associated with the pathophysiological processes of cardiac disease. For example, upregulation of TRIM32 was proven to be beneficial and suggested as a potential therapeutic target for treating pathological hypertrophy and heart failure, while TRIM24 may weaken the TRIM32 cardiac protective effect by protecting dysbindin from the degradation mediated by TRIM32 [93]. TRIM50, located on chromosome 7q11.23, harbors RING, B-box 2, CC, and RFP-like/ B30.2 domains from the N-terminus to the C-terminus, and encodes an E3 ubiquitin ligase.…”
Section: Perspectivementioning
confidence: 99%